Contribution to the Chinese subfamily Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae) VII: New descriptions of Rhaphidophora from Yunnan and Guangxi - Li, Shan; Bian, Xun (Zootaxa, 2024)
This paper contributes further studies Chinese cave crickets and describes seven new species and the female sex of Rhaphidophora longitabula Bian, Zhu & Shi, 2017. All the specimens are deposited in Guangxi Normal University.